Metabolic Engineering of Enterobacter aerogenes for Improved 2,3-Butanediol Production by Manipulating NADH Levels and Overexpressing the Small RNA RyhB - Wu, Yan; Chu, Wanying; Yang, Jiayao; Xu, Yudong; Shen, Qi; Yang, Haoning; Xu, Fangxu; Liu, Yefei; Lu, Ping; Jiang, Ke; Zhao, Hongxin (Frontiers in Microbiology, 2021)
Biotechnological production of 2,3-butanediol (2,3-BD), a versatile platform bio-chemical and a potential biofuel, is limited due to by-product toxicity. In this study, we aimed to redirect the metabolic flux toward 2,3-BD by increasing the NADH pool in E. aerogenes. The enhancement of the NADH/NAD+ ratio by knocking out the NADH dehydrogenase genes (nuoC/nuoD) enhanced 2,3-BD production up to 67% compared with wild-type E. aerogenes. When lactate dehydrogenase (ldhA) was knocked out, the yield of 2,3-BD was increased by 71.2% compared to the wild-type. Metabolic flux analysis revealed that up-regulated expression of the sRNA RyhB led to a noteworthy shift in metabolism. The 2,3-BD titer of the best mutant Ea-2 was almost 7 times higher than that of the parent strain in a 5-L fermenter. In this study, an effective metabolic engineering strategy for improved 2,3-BD production was demonstrated by increasing the NADH/NAD+ ratio and blocking competing pathways.